PANAS DAN KENYAMANAN IKLIM MIKRO AKIBAT SIFAT BAHAN PERKERASAN PELAPIS PERMUKAAN RUANG LUAR DI DAERAH BERIKLIM TROPIS LEMBAB (Heat and Comfort of Micro Climate due to Thermal Properties of Hard Materials of Ground Surface in Humid Tropics Environment) - Sangkertadi, Prof.; Syafriny, Reny (Department of Architecture, Engineering Faculty - Sam Ratulangi University, 2013)
Architect or urban designer’s major task is to create the best possible outdoor environment to the people’s activities. Environmental-friendly technology appreciation in the context of urban architecture may be interpreted as the application of materials covering buildings envelop and ground surface. Soft and hard materials covering park space, roofing and envelop wall, play important role determining convective and radiant temperature of its environment. Outdoor thermal comfort that influenced by ambiance temperature, is therefore depends on utilization of surface material.This paper contains the intention of thermal performance of outdoor environment in a tropical and humid environment with a case of the city of Manado, Indonesia. One hour steps of temperature measurement at the surface of hard materials for ground covering (asphalt and concrete block) without solar shading in a hot season were done. Air temperature of outdoor space was also recorded. This is to know the effect of using different types of materials on outdoor environment. Some of calculations were also realized in order to make comparison with the results from measurement and to know the quantity of outdoor comfort level of the environment. This study recommend of principles of thermal properties of materials for ground covering of a tropical environment.